KEARIFAN LOKAL MASYARAKAT ADAT SAMBORI SEBAGAI PENGUAT IDENTITAS NASIONAL - Nurlatifa Nurlatifa (Jurusan P. IPS, FKIP, Universitas Mataram, 2022)
The Sambori Indigenous People are a community known for their local wisdom. This study aims to find out the local wisdom of the Sambori Indigenous People and how to continue to preserve the local wisdom of the Sambori Indigenous People as a reinforcement of national identity. This research uses a literature study method with data analysis techniques using this analysis technique. The conclusion of this study is that the Sambori Indigenous People have several local pearls of wisdom, namely the Pamali Manggodo Tradition, Uma Lengge Sambori, Rimpu, Rawa Mbojo, Nggana ra Nggoa Traditional Ceremony (Birth), Suna ro Ndoso Traditional Ceremony (Circumcision), Nika ra Neku Traditional Ceremony (Wedding), Ampa Fare Ceremony (ceremonies of the growing and harvesting seasons). The local wisdom of the Sambori Indigenous People can be preserved as a reinforcement of national identity by means of social counseling, the establishment of customary forums, and the procurement of cultural festivals.